Influence of substrate temperatures on structural, morphological and optical properties of RF-sputtered anatase Tio 2 films - Hasan, M.M.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan; Saidur, Rahman; Abd Shukor, Mohd Hamdi (Arabian Journal for Science and Engineering, 2010)
In this investigation, TiO 2 thin films were deposited on glass substrates at varying substrate temperatures from room temperature to 300 Â°C by radio-frequency (RF) magnetron sputtering at an elevated sputtering pressure of 3 Pa. As-deposited TiO 2 films were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), field emission Auger electron microscopy (FEAES), and UV-visible-NIR spectrophotometry. The XRD results reveal that all the as-deposited films possessing the anatase structure and crystallinity of TiO 2 films appears to deteriorate slightly at higher substrate temperatures. The crystallite size of the as-deposited films at different substrate temperatures is ~44 nm, which shows insignificant variation. AFM images exhibit a similar type of nodular morphology in the as-grown films. TiO 2 films deposited at different substrate temperatures exhibit high visible transmittance and a high refractive index ranging from 2.31 to 2.37 at a wavelength of 550 nm. The optical band gap of the films has been estimated to be in the range from 3.39 to 3.42 eV.